Effect Of Work Flexibility and Work Specialization On Employee Satisfaction at CV. Gunodia Family In Mukomuko Regency - Gustian Afrijal; Tri Febriana Melinda; Yanto Effendi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims analyze the effect of work flexibility and work specialization, both partially and simultaneously, on employee satisfaction. Methodology: This reserach inidercritive quantiative with a census sampling technique. Data collection was conducted through questionnaires. The analysis methods used included validity tests, reliability tests, multiple linear regression, r tests, t tests, and f tests. Results: Work flexibility does not have a significant effect on employee satisfaction. Work specialization has a positive and significant effect Simultaneously, work flexibility and work specialization had a significant effect with Findings: The study found that the division of work according to expertise and responsibility increased job satisfaction, while work flexibility had no effect because it was influenced by job characteristics. Novelty: This study provides new empirical insights into the relevance of flexibility and job specialization in field operations companies such as CV. Gunodia. Originality: The originality of this research lies in the context of the object and the combination of variables that have not been studied in this company. Conclusion: Work specialization has been proven to be a dominant factor in increasing job satisfaction, while work flexibility does not have a significant effect. Type of Paper: Research article.